To factor the polynomial expression \(7x^2 + 42x + 63 = 0\), we can start by factoring out the greatest common factor (GCF):
- Identify the GCF of the coefficients (7, 42, and 63). The GCF is 7.
- Factor out 7:
\[ 7(x^2 + 6x + 9) = 0 \]
- Now, we can focus on factoring the quadratic \(x^2 + 6x + 9\). This trinomial can be factored as:
\[ (x + 3)(x + 3) = (x + 3)^2 \]
- Substitute this back into the equation:
\[ 7(x + 3)^2 = 0 \]
- Now, divide both sides by 7:
\[ (x + 3)^2 = 0 \]
- Take the square root of both sides:
\[ x + 3 = 0 \]
- Finally, solve for \(x\):
\[ x = -3 \]
Thus, the solution for the polynomial equation \(7x^2 + 42x + 63 = 0\) is:
\[ \boxed{-3} \]